Rights to Oloran Land (aanslibbing) in Ujungpangkah District, Gresik Regency Prespective of Traditional Land Law in National Land Law System - Suyanto Suyanto (Faculty of Law, Universitas Pekalongan, 2023)
The control of oloran land rights (aanslibbing) in the community of Ujung Pangkah Subdistrict, Gresik Regency, East Java Province from the past until now has led to the conception of customary land ownership, which is hereditary based on customary law that applies in the community, namely obtained a seal letter from the Village Head p. This resulted in local regulation (self regulation) as customary land law, with the principle that oloran land is customary land that does not have a conceptual arrangement that is recognized and respected by the state as state land.This research is a normative research aimed at providing answers to the legal vacuum that regulates the granting of oloran land rights originating from customary law by using a statutory approach and a conceptual approach.The results of this study found that the UUPA which regulates national land law provides land recognition for oloran land (aanslibbing) which is sourced from customary land law as state land which can be applied for rights by using the provisions in the Regulation of the Head of BPN Number 9 of 1999 by giving the first rights in the form of Ownership Rights, Use Rights and Building Use Rights.